Production and stability of Oxygen-18 labeled Caribbean ciguatoxins and gambierones. (May 2022) - Mudge, Elizabeth M.; Meija, Juris; Uhlig, Silvio; Robertson, Alison; McCarron, Pearse; Miles, Christopher O.
Abstract: Ciguatoxins (CTXs) and gambierones are ladder-shaped polyethers associated with ciguatera poisoning and Gambierdiscus spp. Several of these compounds contain carbonyl or hemiketal groups, which have the potential to exchange with 18 O-labeled water under acidic conditions. The effects of solvent composition and acid on the rate of exchange and on the stability of the labels at various pH values were assessed to optimize the incorporation of 18 O into Caribbean ciguatoxin-1 and -2 (C-CTX1/2), gambierone, and 44-methylgambierone. LC−HRMS results showed that 18 O-labeling occurred at the hydroxy group of the hemiketal at C-56 in C-CTX1/2, and at the hydroxy group of the hemiketal at C-4 and the ketone at C-40 in gambierones. Labeling occurred very rapidly (complete in <30 min) for C-CTX1/2, and more slowly (complete in ca. 16 h) for both gambierones. Labeled C-CTX1/2 was reduced with sodium borohydride to produce 18 O-labeled C-CTX3/4. The incorporated 18 O labels in the gambierones and C-CTXs were retained in aqueous solvent mixtures under neutral conditions in a short-term stability study, demonstrating that these 18 O-labeled toxins have the potential to be used in isotope dilution and metabolism studies. Graphical abstract: Image 1 Highlights: Methodologies developed for 18 O exchange with H2 18 O to produce labeled C-CTX1/2 and gambierones. Borohydride reduction of [ 18 O]C-CTX1/2 produced stable [ 18 O]C-CTX3/4. pH stability suggested 18 O-labeled CTXs and gambierones maintained under neutral conditions.